A panther's scream [large type] - Gear, W. Michael (Gear, W. Michael, Saga of the Mountain Sage, 2024)
Having made the decision to leave Richard and the whites, Willow packs, only to discover that all of the expedition's horses, including her own, have been stolen--a fact the scarred hunter, Travis Hartman can't abide! For Richard, the pursuit of the thieves and recovery of the animals will leave him forever changed. Meanwhile, the Arikara make their move on Maria, ending in a bloody battle where Willow crosses a line she never anticipated. Reunited with a wounded Richard, she struggles to save his life. But some bridges cannot be crossed. Heartbroken, she leaves in the desperate hopes of returning to her people. Only to face her biggest challenge yet when a Blackfeet raiding party crosses her path, for they have a captive too dear to her heart to let die. As the Maria struggles to ascend the Yellowstone, Dave Green will meet the end of all his dreams. And Richard will face the wilderness alone, and battle for his very life.